STRATEGI PEMBERITAAN MEDIA ONLINE LPP RRI SURAKARTA DALAM MEMPERTAHANKAN EKSISTENSINYA - Rahmalia, Sinta; Suryo, Herning; Muadz, Muadz (Solidaritas, 2024)
This study examines the Online Media Reporting Strategy of LPP RRI Surakarta in Maintaining Its Existence. This type of research is descriptive qualitative with primary data sources in the form of observations, interviews and documentation as well as secondary data sources by conducting literature studies and document studies. The informants in this study are broadcast administrators, associate experts as well as editors at LPP RRI Surakarta and also RRI online media news readers who are students, informant determination techniques using purposive sampling techniques. The data was then analyzed using Miles and Huberman's data analysis techniques, namely data reduction, data presentation and data verification. The results of this study are strategies used by LPP RRI Surakarta in choosing issues to be raised as a news including: 1) Carry out company procedures to prioritize actual issues, 2) Choose issues based on the principle of usefulness to readers, 3) Conduct direct investigations into the field, the types of news published are straight news and new features, with rubrics: news, economics, law, sports, and lifestyle, the news presentation strategy applied is to apply separate standards and there are 3 elements that are used as criteria in LPP RRI Surakarta to assess feasibility News, which contains elements of novelty, is important and interesting. Keywords: news strategy, presence, online media